2022
DOI: 10.21203/rs.3.rs-1923784/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dimensional Structure of one-year Post-COVID-19 Neuropsychiatric and Somatic Sequelae and Association with Role Impairment

Abstract: This study examined the latent structure of the broad range of complex neuropsychiatric morbidities occurring one year after COVID-19 infection. As part of the CU-COVID19 study, 248 (response rate = 39·3%) of 631 adults hospitalized for COVID-19 infection in Hong Kong completed an online survey between 3-2021 and 1-2022. Disorder prevalence was compared against a random non-infected household sample (n = 1837). 248 surveys were received on average 321 days post-infection (Mean age: 48·9, 54% female, moderate/s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…While other studies have shown similar results, the limitations in the designs of such studies, namely in terms of the potential for reverse causality, have made it difficult to draw such conclusions straightforwardly from their results. A study from Hong Kong, for example, reported financial worry as one of the predictors of post-COVID mental health trajectory [27]. Because they only measured the subjects' evaluation of their financial situation post-COVID, however, there is difficulty determining the direction of causality given that a self-reported concern about financial status can be secondary to and a result of poor mental and physical health.…”
Section: Increase In Medical Diagnoses and Medical Resource Utilisati...mentioning
confidence: 99%
See 1 more Smart Citation
“…While other studies have shown similar results, the limitations in the designs of such studies, namely in terms of the potential for reverse causality, have made it difficult to draw such conclusions straightforwardly from their results. A study from Hong Kong, for example, reported financial worry as one of the predictors of post-COVID mental health trajectory [27]. Because they only measured the subjects' evaluation of their financial situation post-COVID, however, there is difficulty determining the direction of causality given that a self-reported concern about financial status can be secondary to and a result of poor mental and physical health.…”
Section: Increase In Medical Diagnoses and Medical Resource Utilisati...mentioning
confidence: 99%
“…Contrary to our hypothesis, the severity of the index infection did not predict whether there would be a high or low load of chronic neuropsychiatric symptoms post-COVID. Available evidence on the ability of infection severity to predict PACS has not been consistent [27,[29][30][31][32]. There is convergent evidence, however, that persistent PACS can occur in individuals with mild infections.…”
Section: Increase In Medical Diagnoses and Medical Resource Utilisati...mentioning
confidence: 99%
“…Contrary to our hypothesis, the severity of the index infection did not predict whether there would be a high or low load of chronic neuropsychiatric symptoms post-COVID. Available evidence on the ability of infection severity to predict PACS has not been consistent (27,(29)(30)(31)(32). There is convergent evidence, however, that persistent PACS can occur in individuals with mild infections.…”
Section: Post-covid Subjects With Multiple Neuropsychiatric Complaint...mentioning
confidence: 99%